ANALYSIS OF RHODAMINE B IN LIP CREAM USING COLORIMETRIC METHOD BY DIGITAL IMAGING - Jauhar Fatin Muna; Riska Yudhistia Asworo (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2023)
Background: lip cream is one type of lip color often used by women. Beside it, there are still some manufacturers add Rhodamine B to lip color, especially lip cream. This is very dangerous for the health of consumers. Therefore, it is necessary to analysis of Rhodamine B in samples red lip cream. Objective: the purpose of this research to analysis Rhodamin B contained in lip cream using colorimetric method by digital imaging. Method: the method of this research is colorimetric method by digital imaging. This method is a simple, low budget, easy, and fast method. Result: the standard curve Zn-thiocyanate-Rhodamine B solution of RGB components, shows the result is green component curve has a good R2 value is 0,9992 with the linear regression equation y = 0,0423x + 0,1335. Accuracy expressed as % recovery, shows good results with an average value of 100,7%. Determination of the precision value also shows good result, the RSD value obatained is 1,96%. So that, the colorimetric method by digital imaging can be used to analysis of Rhodamine B in samples. Conclusions: sample A and B positive Rhodamine B with concentrations of 0,6730 ppm and 0,0488 ppm.